β-elemene Isopropanolamine Derivative LXX-8250 Induces Apoptosis Through Impairing Autophagic Flux via PFKFB4 Repression in Melanoma Cells - Jalal, Sajid; Zhang, Ting; Deng, Jia; Wang, Jie; Xu, Ting; Zhang, Tianhua; Zhai, Chuanxin; Yuan, Ruqiang; Teng, Hongming; Huang, Lin (Frontiers in Pharmacology, 2022)
Melanoma is a highly aggressive skin cancer and accounts for most of the skin cancer-related deaths. The efficacy of current therapies for melanoma remains to be improved. The isopropanolamine derivative of β-elemene LXX-8250 was reported to present better water solubility and stronger toxicity to tumor cells than β-elemene. Herein, LXX-8250 treatment showed 4-5-fold more toxicity to melanoma cells than the well-known anti-melanoma drug, Dacarbazine. LXX-8250 treatment induced apoptosis remarkably, which was caused by the impairment of autophagic flux. To clarify the molecular mechanism, microarray analyses were conducted, and PFKFB4 expression was found to be suppressed by LXX-8250 treatment. The cells overexpressed with PFKFB4 exhibited resistance to apoptosis induction and autophagic flux inhibition by LXX-8250 treatment. Moreover, LXX-8250 treatment suppressed glycolysis, to which the cells overexpressed with PFKFB4 were tolerant. LXX-8250 treatment inhibited the growth of melanoma xenografts and suppressed PFKFB4 expression and glycolysis in vivo. Taken together, LXX-8250 treatment induced apoptosis through inhibiting autophagic flux and glycolysis in melanoma cells, which was mediated by suppression of PFKFB4 expression. The study provides a novel strategy to melanoma treatment.